Peran Kepemimpinan dalam Pendidikan Global - Iza Faridatul Amalia; Daman Daman; Asmaul Husna; Rodia Tammardiah Hasibuan; Sasmiyarti Sasmiyarti; Alfroki Martha (Journal on Education, 2024)
Leadership is a process used to influence, direct, and nurture others to achieve goals that we want to achieve together. The objectives of educational leadership in schools consist of: improving the quality of the process of student learning outcomes continuously, the availability of a school vision, the coordination of school residents in realizing the vision, the optimal empowerment of teachers, the development of teachers' careers and the high performance of the school. Leadership in education not only influences student outcomes, but also shapes the culture, values, and future direction of the education system. This study aims to find out the role of leaders and leadership styles in education. The methods used in this study are qualitative research which includes literature studies, and documentaries.